Micronuclei and other nuclear abnormalities in the oral epithelium of female workers exposed to pesticides. - Castro, Rocío (2004)
In order to study if banana fields labour exposure to pesticides produces some kind of DNA damage, we determine the presence of micronuclei in epithelial oral cells in working women in Guapiles and Siquirres, Costa Rica, as an effect biomarker. We also analyzed other abnormalities in the nucleus of those cells such as broken-egg, karyolysis or kariorrhexis, to see if there was some kind of genotoxicity or citotoxicity. The women group exposed to pesticides worked in packing bananas plant from different independent farms. The control group of women had never done any farming tasks; they did not live in the banana fields, neither their husband. We got information about the life style, medical and familial history of the participants through an interview. We did not found any significant increment in the frequency of micronuclei form the exposed group compared with the controls. The other nuclei abnormalities showed signs of citotoxicity or genotoxicity in the controls, associated with the intake of coffee and dental x-rays. These results do not rule out at that pesticides used in packing bananas are agents capable of producing damage to the DNA, but it seems that micronuclei from the oral epithelium is not the most adequate marker to measure it.